Secure vehicular digital forensics system based on blockchain - Meng LI; Chengxiang SI; Liehuang ZHU (物联网学报)
The emergence of vehicular big data has brought a great promotion to better understand characteristics of vehicular networks,grasp needs of users and improve service qualities.However,malicious users and criminals leverage vehicular networks to conduct illegal behaviors,resulting in a decline in the service quality and difficulties in determining the liability in vehicle accidents.At the same time,there are still some security and privacy issues in the vehicular digital forensics,such as the identity privacy of the data provider and the request control of the data requester.Therefore,a secure vehicular digital forensics scheme based on blockchain was proposed.Firstly,a data requester registered with a certificate authority and an anonymous certificate was obtained for the subsequent data uploading.Then,the data user obtained the public-private key pair and user key in registration,which were respectively used for the data requesting and data decryption.Only if certain attributes were held,the right plaintext could be decrypted.Next,a consortium blockchain was jointly established by several institutions with high credibility to record all data transactions.Finally,the security and privacy were experimentally analyzed,and the performance was tested based on the Ethereum platform.